Broad-spectrum XX and XY gonadal dysgenesis in patients with a homozygous L193S variant in PPP2R3C. Issue 1 (1st December 2021) - Cicek, Dilek; Warr, Nick; Yesil, Gozde; Kocak Eker, Hatice; Bas, Firdevs; Poyrazoglu, Sukran; Darendeliler, Feyza; Direk, Gul; Hatipoglu, Nihal; Eltan, Mehmet; Yavas Abali, Zehra; Gurpinar Tosun, Busra; et al.
Abstract: Context: Homozygous and heterozygous variants in PPP2R3C are associated with syndromic 46, XY complete gonadal dysgenesis (Myo-Ectodermo-Gonadal Dysgenesis (MEGD) syndrome), and impaired spermatogenesis, respectively. This study expands the role of PPP2R3C in the aetiology of gonadal dysgenesis (GD). Method: We sequenced the PPP2R3C gene in four new patients from three unrelated families. The clinical, laboratory, and molecular characteristics were investigated. We have also determined the requirement for Ppp2r3c in mice (C57BL6/N) using CRISPR/Cas9 genome editing. Results: A homozygous c.578T>C (p.L193S) PPP2R3C variant was identified in one 46, XX girl with primary gonadal insufficiency, two girls with 46, XY complete GD, and one undervirilised boy with 46, XY partial GD. The patients with complete GD had low gonadal and adrenal androgens, low anti-Müllerian hormone, and high follicle-stimulating hormone and luteinizing hormone concentrations. All patients manifested characteristic features of MEGD syndrome. Heterozygous Ppp2r3c knockout mice appeared overtly normal and fertile. Inspection of homozygous embryos at 14.5, 9.5, and 8.5 days post coitum (dpc) revealed evidence of dead embryos. We conclude that loss of function of Ppp2r3c is not compatible with viability in mice and results in embryonic death from 7.5 dpc or earlier. Conclusion: Our data indicate the essential roles for PPP2R3C in mouse and human development. Germline homozygous variants in human PPP2R3C are associated with distinctive syndromic GD of varying severity in both 46, XY and 46, XX individuals.